Global Existence of the Higher-Dimensional Linear System of Thermoviscoelasticity - Zhiyong Ma (International Journal of Differential Equations)
We obtain a global existence result for the higher-dimensional thermoviscoelastic equations. Using semigroup approach, we will establish the global existence of homogeneous, nonhomogeneous, linear, semilinear, and nonlinear, thermoviscoelastic systems.